Recent crustal movements, 1982 : proceedings of the Third Symposium on Recent Crustal Movements and Phenomena Associated with Earthquakes and Volcanism, May 12-13, 1982, Tokyo, at the General Meeting of the International Association of Geodesy - Vyskocil, P. (Pavel); Wassef, A. M.; Green, R. (Ronald) (Developments in geotectonics, 1983)
Recent Crustal Movements, 1982.